Effects of glutathione therapy on chronic viral hepatits B and hepatits C - Senol, Arzu; Cambay, Zafer (Parlar Scientific Publications, 2020)
In this study, serum levels of glutathione (GSH), which is thought to have significant effects on both liver inflammation and follow-up of the disease progression in cases with chronic hepatitis B (CHB) and chronic hepatitis C (CHC), were examined. The study included 85 patients with CHB (46 were female, 39 were male; with an age range of 41.7±14.3) (group 1), 35 patients with CHC (13 were female, 22 were male; with an age range of 44.1±12.7) (group 2), and 30 healthy individuals with no chronic disease (12 were female, 18 were male; with an age range of 37.4±15.6) (control group). The serum levels of glutathione of the patients were determined via enzyme-linked immunosorbent assay (ELISA) method (R&D Systems, Minneapolis, MN, USA). There was no statistically significant difference between the patient groups in terms of serum levels of GSH (p>0.05). However, GSH levels were found to be statistically significantly lower in the patients groups than in the control group (p<0.05). There was no statistically significant difference between GSH levels and histological activity index (HAI), fibrosis, and viral load in the patient groups (p>0.05). Compared to the control group, patients with CHB and CHC has been found to have low levels of GSH, which has showed that GSH has an important role in liver inflammation and tissue damage. Glutathione can be used in the diagnosis and follow-up processed as a marker of inflammation. Furthermore, treatments for increasing the GSH levels may positively contribute to the treatment of CHB and CHC cases in terms of the prevention of viral replication and tissue damage. There is a need for large-scale studies including treatment. © by PSP
Keywords: Chronic Hepatitis B; Chronic Hepatitis C; Glutathione